A national system of biological monitoring in the Russian Arctic as a tool for the implementation of the Stockholm Convention - Tatiana Yu Sorokina
Abstract Issues related to protection of the Arctic environment are becoming increasingly urgent, as arctic ecosystems are vulnerable to increasing anthropogenic pressures. The problem of protecting Northern nature from the effects of persistent organic pollutants, which are dangerous for both biota and human health, is particularly acute. This case study analyses the existing normative acts regulating monitoring activities in the Russian Arctic. The paper emphasizes gaps in legal regulation, which are particularly prominent with regard to monitoring the quality of traditional food consumed by indigenous peoples. The author introduces proposals to change the current legislation to improve the efficiency of the state monitoring system in the Russian Arctic. Such changes will also help to harmonize monitoring activities in Russia with other Arctic States and to fill in the gaps in the Global Monitoring Reports and the Arctic Monitoring and Assessment Programme (AMAP) reports on persistent organic pollutants in traditional indigenous food. Stockholm Convention, Russian Arctic, Environmental monitoring, AMAP